Characterization of reflectivity inversion, α- and β-phase transitions and nanostructure formation in hydrogen activated thin pd films on silicon based substrates - Kalli, Kyriacos; Othonos, Andreas S.; Christofidès, Constantinos (My University, 2002)
Optically thin palladium metal films evaporated on different silicon based substrates are investigated following exposure to different concentrations of hydrogen gas in air. Laser modulated reflectance off the palladium surface of silicon oxide and silicon nitride substrates is used to recover information regarding the reflectivity inversion and α/β-phases of the palladium complex after both first and multiple gas cycling. Atomic force microscopy confirms the formation of metal nanostructures following exposure to hydrogen of the optically thin palladium films.
Keywords: Hydrogen; Palladium; Silicon; Nanostructured materials